Association of TIM-3 with anterior uveitis and associated systemic immune diseases: a Mendelian randomization analysis - Lin, Dan; Zhu, Rong-Cheng; Tang, Chun; Li, Fen-Fen; Gao, Mei-Ling; Wang, Yu-Qin (Frontiers in Medicine, 2023)
Background: We aimed to investigate the causal association between TIM-3, an immune checkpoint inhibitor, and anterior uveitis (AU), as well as associated systemic immune diseases. Materials and methods: We performed two-sample Mendelian randomization (MR) analyses to estimate the causal effects of TIM-3 on AU and three associated systemic diseases, ankylosing spondylitis (AS), Crohn’s disease (CD) and ulcerative colitis (UC). Single-nucleotide polymorphisms (SNPs) associated with AU, AS, CD, and UC were selected as the outcomes: AU GWAS with 2,752 patients with anterior AU accompanied with AS (cases) and 3,836 AS patients (controls), AS GWAS with 968 cases and 336,191 controls, CD GWAS with 1,032 cases and 336,127 controls, and UC GWAS with 2,439 cases and 460,494 controls. The TIM-3 dataset was used as the exposure (n = 31,684). Four MR methods (namely, inverse-variance weighting (IVW), MR-Egger regression, weighted median, and weighted mode) were used in this study. Comprehensive sensitivity analyses were conducted to estimate the robustness of identified associations and the potential impact of horizontal pleiotropy. Results: Our studies show that TIM-3 is significantly associated with CD (OR = 1.001, 95% CI = 1.0002-1.0018, P-value = 0.011). We also found that TIM-3 may be a protective factor for AU, although these results lacked significance (OR = 0.889, 95% CI = 0.631-1.252, P-value = 0.5). Genetic predisposition to particular TIM-3 expression is not associated with AS or UC susceptibility. No potential heterogeneities or directional pleiotropies were observed in our analyses. Conclusion: According to our study, a small but significant correlation was observed between TIM-3 expression and CD susceptibility. Additional studies in different ethnic backgrounds will be necessary to further explore the potential roles and mechanisms of TIM-3 in CD.